Viral Lobbying : Strategies, Access and Influence During the COVID-19 Pandemic. - Crepaz, Michele. (Viral Politics Series, 2022)
This series addresses viral politics with an initial focus on the 'COVID-phenomenon': more than a viral infection, COVID-19 has impacted how scientists find solutions, what governments do, and how societies react.